The role of women in artisanal fishing on the Oléria River, Marajó archipelago, Brazil (Research, Society and Development, 2021)
Fishing women in Brazil are still “invisible” in the eyes of contemporary society. It is with this perspective, that this work analyzed the role of riverside women in artisanal fishing in the Marajó archipelago (state of Pará, Brazil). The research was carried out in the Santo Antônio community in the municipality of Breves, located on the Oléria river. The methodological procedure used was bibliographic research and questionnaires with twenty women who practice fishing along this river. Data collection took place in January 2020. The information was analyzed using a simple description. The research revealed that even though women engaged in various fishing-related activities, they are usually represented by their husbands or children and their activity is seen as an aid. Therefore, there is a need for these women to have greater visibility so that Marajoara society can value them once their work in artisanal fishing is fundamental for their subsistence and that of their social group.